STRATEGI PEMBELAJARAN PAI BAGI ANAK TUNARUNGU MASA PANDEMI COVID 19 PADA JENJANG SEKOLAH MENENGAH PERTAMA Â DI SKH YKDW 02 KOTA TANGERANG - Kapitanhitu, Nyimas Nuraini; Haromaini, Ahmad; Halimah, Nur (Universitas Islam Syekh-Yusuf, 2021)
This research was conducted at the Karya Dharma Wanita Foundation Special School 02 Tangerang City. This study aims to find out how the PAI learning strategy for deaf children during the COVID-19 pandemic at the junior high school level at Special School YKDW 02 Tangerang City. This type of research is Field Research or field research. The approach used in this research is a descriptive qualitative research approach. Sources of data in this study include primary and secondary sources. This data collection is done through interviews, observation, and documentation. The results of this study indicate that the strategies used by teachers in learning Islamic religious education during the COVID-19 pandemic at SKh YKDW 02 Tangerang City, are conventional strategies, conventional strategies, namely learning strategies where PAI teachers dominate the learning process, This can be seen from the activities (1) opening learning, (2) delivering material carried out by the teacher, that the PAI learning strategy during the pandemic is not much different from face-to-face learning, it's just that in delivering the material the teacher uses the google meet application and whatsapp videocall , the language used is simpler, and the pronunciation must be seen clearly and slowly, (3) closing the lesson.